Unwrapped hydroxyapatite orbital implants: our experience in 347 cases - Sobti, Manvi M. (Eye (Lond), 2019)
OBJECTIVES: To report the results of a large case series of enucleations with primary insertion of an unwrapped hydroxyapatite (HA) orbital implant. METHODS: We retrospectively reviewed consecutive enucleations with primary orbital (HA) implant insertion performed at the Scottish Ocular Oncology Service, Glasgow between 1990 and 2014. The unwrapped hydroxyapatite orbital implant was placed in the posterior portion of the socket and recti muscles sutured end-to-end over the implant. RESULTS: Out of 347 consecutive enucleations, the indication for enucleation was tumour-related pathology in 59.7% and painful blind eye in 40.3%. Majority (70%) received an implant of 22-mm diameter. At an average follow-up of 3.5 years, complications included post-enucleation socket syndrome (11.5%), chronic discharge (9.2%), chronic pain (4.3%), recurrent conjunctival infection (2.3%),conjunctival cysts (2%), contracted socket (1.4%), implant exposure (1.2%), haematoma (0.6%) and ill-fitting prosthesis (0.6%). Implant exposure (1.2%, n = 4) occurred at a mean of 4.5 months post surgery and was managed by temporalis fascia graft (n = 1), tarsoconjunctival flap (n = 1), implant removal (n = 1) and observation (n = 1). Overall, 9.8% of patients needed further surgery including lower lid tightening (4.3%), ptosis repair (2.3%), conjunctival cyst excision (1.2%), fornix reconstruction (1.2%), graft/flap for exposure (0.6%) and implant removal (0.3%). CONCLUSIONS: A low rate of implant exposure indicates that absence of wrapping material around hydroxyapatite orbital implants does not compromise surgical outcomes and has the added benefit of reduced surgical time and avoidance of complications from wrapping materials. Posterior implant placement and end-to-end recti suturing contribute to the success of the procedure.